Sex differences in the pharmacokinetics and bioequivalence of the delayed‐release combination of doxylamine succinate‐pyridoxine hydrochloride; implications for pharmacotherapy in pregnancy. (10th October 2013) - Koren, Gideon; Vranderick, Manon; Gill, Simerpal K.; Macleod, Stuart
Abstract Most bioequivalence (BE) studies are conducted in males with the assumption that variability in pharmacokinetics is similar between the sexes. The purpose of this single‐center, reference replicate study was to determine the effect of sex on the pharmacokinetics and BE of doxylamine–pyridoxine 10 mg–10 mg delayed‐release tablets. Healthy males (n = 12) and non‐pregnant females (n = 12) were administered two tablets, and blood sampling was conducted from 1 hour pre‐dose until 72 hours post‐dose. After 21 days, dose administration and blood sampling were re‐conducted. All analytes were measured using liquid chromatography‐tandem mass‐spectrometry. Pharmacokinetic parameters were calculated for each study period using standard, non‐compartmental methods, and differences were assessed using ANOVA. BE testing was conducted using the relative 90% confidence interval for the AUC0−t for each analyte. Females had significantly larger AUC0−t for doxylamine, 1, 550 ng h/mL (coefficient of variance [CV = 19%]) versus 1, 272 ng h/mL (CV = 21%; P ≤ .05), and pyridoxine, 35 ng h/mL, (CV = 43%) versus 25 ng h/mL (CV = 31%; P ≤ .05) compared to males. A higher Cmax for doxylamine was observed in females, 107 ng/mL (CV = 16%), compared to males, 86 ng/mL (CV = 15%) (P ≤ .05). BE testing did not demonstrate bioequivalence between males and females. Pharmacokinetic differences observed between the sexes have implications for future BE studies using doxylamine–pyridoxine.